Which scoring systems are useful for predicting the prognosis of lower gastrointestinal bleeding? Old and new - Ku Bean Jeong; Hee Seok Moon; Kyung Ryun In; Sun Hyung Kang; Jae kyu Sung; Hyun Yong Jeong (BMC Gastroenterology)
Abstract Background The incidence of lower gastrointestinal bleeding is on the rise, prompting the creation of various scoring systems to forecast patient’s outcomes. But there is no single unified scoring system and these scoring systems clinical data are small and not worldwide. Aims To evaluate how different scoring systems predict mortality and prolonged hospital stay (≥ 10 days). Methods A retrospective review was conducted on the medical records of 4417 patients who presented with hematochezia at the emergency department from January 2016 to December 2022. We evaluated the predictive accuracy of various scoring systems for 30-day mortality and prolonged hospital stay (≥ 10 days) by analyzing the areas under the receiver-operating characteristic curves, taking into account factors such as patient age, laboratory findings, and comorbidities (ABC); AIMS 65; Glasgow-Blatchford; Oakland; Rockall(pre-endoscopy); SHA2PE; and CHAMPS scores. Results We analyzed data from 1000 patients (mean age 66 years, 56.1% men, mean hospital stay 9.4 days) with lower gastrointestinal bleeding confirmed by any other means including DRE, colonoscopy and CT. The 30-day mortality rate was 3.7%. The primary etiologies of lower gastrointestinal bleeding were identified as ischemic colitis and diverticular bleeding, accounting for 18.8% and 18.5% of cases, respectively. In terms of forecasting 30-day mortality, the AIMS 65, CHAMPS, and ABC scoring systems demonstrated superior performance (p < 0.001). For predicting prolonged hospital stay, the SHA2PE score exhibited the highest accuracy among all evaluated systems (p < 0.001). Conclusions The newly developed scoring systems demonstrated superior accuracy in forecasting outcomes for patients with lower gastrointestinal bleeding, and the results of this study demonstrate that these scoring systems can be applied in clinical practice.